PERANAN AUGMENTED REALITY DALAM PENGENALAN HURUF DAN ANGKA PADA ANAK- ANAK PRE-SCHOOL - Yudi Antonie Stevanus Soegito (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
The development of education in this modern era and digitalization, is developing towards a more perfect and balanced direction in life that is needed by every individual. Education is needed to be fulfilled to carry out the maturation process individually and in society. Education is considered veryimportant and should be given to early childhood, namely the age of 0-6 years, which is an important age in physical and psychological development. These developments still require parental participation in maximizing existing formal and non-formal educational institutions. At the age of 0-6 years,children are still thinking concretely, so they need interesting, informative learning media in explaining the abstract so that the material can be understood by children. In this era of digitalization technology, many technological innovations have emerged that are used as learning media in the form of Augmented Reality. AR (Augmented Reality) technology was chosen as one of the learning media that can improve the quality of education, especially the level of understanding of early childhood. This study uses Augmented Reality technology in introducing letters and numbers to 47 pre-school students, using experimental methods in implementing this Augmented Reality application. This application is intended to provide a significant improvement in understanding and recognition of Letters and Numbers, and to provide children's interest in learning